A Study of Focal and Segmental Glomerulosclerosis according to the Columbia Classification and Its Correlation with the Clinical Outcome - Nuguri, Swapna; Swain, Meenakshi; Padua, Michelle de; Gowrishankar, Swarnalata (Journal of Laboratory Physicians, 2023)
Introduction Focal and segmental glomerulosclerosis (FSGS) is a leading cause of nephrotic syndrome in both adults and children. The “Columbia classification of FSGS” includes five variants; not otherwise specified (NOS), tip, perihilar, cellular, and collapsing variants that may have different prognostic and therapeutic implications.Materials and Methods This is a retrospective study and was carried out in the Department of Histopathology, Apollo Hospitals, Hyderabad. Of a total of 11,691 kidney biopsies over a 7-year period, from 2006 to 2012, 824 cases were diagnosed as FSGS, of which 610 cases in which detailed clinical findings were available were included in this study. FSGS was then categorized according to the Columbia classification.Results FSGS, NOS was the predominant histomorphological variant. Serum creatinine was significantly high in the collapsing variant, followed by NOS. Follow-up data was available for 103 cases,72.8% had complete remission, 10.6% had partial remission, and in 16.5 % there was no remission. Relapses were observed in 6.7% cases, two patients (1.9%) succumbed, and 4.8% cases progressed to chronic kidney disease.Conclusion This study showed that perihilar variant was less prevalent, with tip and cellular variants being more prevalent in Indian subcontinent compared to Western literature. Collapsing variant was also less common.
Keywords: FSGS; Columbia classification; focal and segmental glomerulosclerosis